Neural correlates of attentional deficits in Parkinson's disease patients with mild cognitive impairment. (April 2021) - Yang, Jihyun; Pourzinal, Dana; McMahon, Katie L.; Byrne, Gerard J.; Copland, David A.; O'Sullivan, John D.; Dissanayaka, Nadeeka N.
Abstract: Introduction: Deficits in attentional processing observed in Parkinson's disease (PD) patients with mild cognitive impairment (MCI) increase risk of PD dementia. However, the neural basis of these attentional deficits are presently unknown. The present study aimed to explore the neural correlates of attention dysfunction in PD-MCI using the Attention Network Test (ANT) and functional Magnetic Resonance Imaging (fMRI). Method: Fifteen (15) PD-MCI patients, 26 PD patients without MCI (PD-NC) and 22 healthy controls (HC) were scanned (3T Siemens PRISMA) whilst performing the ANT. Reaction time, accuracy and fMRI BOLD activation were compared between groups for the three attentional task components of 1) alerting, 2) orienting, and 3) executive control. Results: PD-MCI patients showed an overall slower reaction time compared to PD-NC and HC, and showed less interference of reaction time in the orienting effect than HC. fMRI data demonstrated greater activation in the bilateral cerebellum crus 1 during the alerting attention condition in both PD-MCI and PD-NC compared to HC. However, activation was supressed in the left postcentral gyrus in PD-MCI compared to PD-NC and HC. Discussion: Alterations in the alerting attention functional network despite intact task performance in PD-MCI suggests that functional brain changes may precede cognitive changes in the attention domain. Furthermore, increased activation in the cerebellum may reflect an attentional compensatory mechanism unique to the PD pathology. Taken together, the findings suggest that PD has a complex effect on attentional ability that can, at least in part, be elucidated using functional neuroimaging. Highlights: Attention Network Test was administered to Parkinson's disease patients and controls under fMRI. Deactivation of left postcentral gyrus despite preserved task performance, during alerting attention. Postcentral gyrus deactivation may precede attention deficits in cognitively impaired patients. Increased cerebellum crus 1 and middle frontal gyrus activation during alerting in PD compared to HC. Cerebellum and middle frontal gyrus activation may reflect PD-specific compensatory mechanisms.